RETHINKING GRAMMAR PEDAGOGY IN THE DIGITAL ERA. EVIDENCE-BASED STRATEGIES FOR 21st -CENTURY LEARNERS - Khodjakulova Feruza (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
The article examines contemporary approaches to teaching grammar in the context of Generation Z and Alpha learners (born 1997–2025). It analyses why traditional deductive methods are losing effectiveness, identifies key psychological, neurocognitive and technological factors that influence modern students, and offers evidence-based strategies: task-based grammar teaching, gamification, implicit learning through meaningful exposure, focus-on-form techniques, and integration of generative AI tools. Special attention is paid to maintaining a balance between conscious rule knowledge and unconscious fluency.